(untitled) (International Journal of Environmental Sciences, 2025)
Food is more than sustenance. It is an expression of one’s traditional and cultural identity. In India regional foods are inter related with local histories, seasonal patterns and native ingredients. Among these, traditional foods of Rayalaseema region in Andhra Pradesh reflect a unique culture shaped by dry climate, variety of crop cultivation and age-old rituals. In the recent times, however, traditional food practices across the country have come under a threat due to factors such as change in the lifestyles, urbanization, migration, fast food culture and disappearing agricultural bio-diversity and Rayalaseema of Andhra Pradesh is no exception. The purpose of this research is to understand the present condition of the traditional food practices of Rayalaseema in Andhra Pradesh, the challenges they face and the ways to revive them. The study uses a qualitative and ethnographic approach that includes field surveys, detailed interviews and hands-on observation. Data was collected from Anantapur, Chittoor, Kadapa and Kurnool districts (areas inclusive of newly formed districts) of Andhra Pradesh. Focusing on senior citizens, farmers, home makers, street vendors, small time food sellers, local cooks and community leaders. The observation includes reviving of a wide range of food items such as seasonal dishes, special foods of festivals and special occasions, foods of wellness importance, day-to-day foods made from cereals, millets, pulses, and locally grown vegetables. This research aims to facilitate extended discussion on food traditions, cooking practices and sustainable development. It serves as a vital resource for policy makers, scholars and NGO’s.